Implementation of Enterprise Architecture in Cloud Computing Companies - Michael, Dennis; Indrajit, Richardus Eko; Dazki, Erick (Sinkron : jurnal dan penelitian teknik informatika, 2022)
In the current era of digitalization, the cloud computing industry market is increasingly shining along with the birth of a number of renewable technologies in this industry. A good and well-planned architectural design for the cloud industry is a major factor in the success of cloud computing companies in competing in a market that has a very broad market share. By conducting research on enterprise architecture, a cloud computing company is expected to provide a different approach to exploring and planning a cloud computing company according to market needs so that it can help or provide different methods and designs that allow us to enter the business world. and business. cloud industry competition. in this digital age. Architectural design planning for companies engaged in the cloud computing industry can use several approaches and tools available in the field so as to simplify, save time and encourage new ideas and initiatives. To be able to achieve the expected goals, it is necessary to conduct several studies and research that is quite intensive so that it can provide significant results and impacts. This research is expected to be one of the means to present a cloud computing architecture that is able to compete in the market and as a whole becomes the concern of all users or researchers. This study aims to discuss Enterprise Architecture related to Cloud Computing companies as providers of modern technology services. Provide information that the technology used is effective and cost-effective for industrial cloud service users. This study uses the TOGAF ADM method in conducting Enterprise Architecture.